How to be a great dad: parental care in a flock of greater flamingo (Phoenicopterus roseus) - Camillo Sandri; Vittoria Vallarin; Carolina Sammarini; Barbara Regaiolli; Alessandra Piccirillo; Caterina Spiezio (PeerJ, 2017)
In the last years, studies on captive greater flamingos have increased. Research on zoo animals is important to improve the knowledge on these species and to improve their ex-situ and in-situ conservation. The aim of the present study was to investigate the parental behaviour of a captive colony of greater flamingo hosted at Parco Natura Viva, an Italian zoological garden, to improve the knowledge on this species in zoos. In particular, the present study investigated and compared the parental care of females and males in 35 breeding pairs of greater flamingos. For each pair, we collected durations of parental care behaviour of both females and males, recording their position in relation to the nest (near the nest, on the nest, away from the nest) and individual and social behaviours performed. First, both partners were involved in parental care and displayed species-specific behaviours reported in the wild. The main results were that males spent more time than females on the nest (P = 0.010) and near it (P = 0.0001) and were more aggressive toward other flamingos than females, both when sitting on the nest (P = 0.003) and when near the nest (P = 0.0003). Therefore, male flamingos seem to be more involved in incubation duties and nest protection than females. This kind of research is important not only to expand the knowledge on bird species such as flamingos, but also to improve their husbandry and breeding in controlled environment. Indeed, understanding animal behaviour allows us to gain insights into their individual and social needs, addressing potential animal welfare issues.